2008
DOI: 10.1007/s00109-008-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging hurdles in stem cell therapy for peripheral vascular disease

Abstract: Indeed, while questions about safety, dose and administration route/timing/frequency are the first ones to be addressed when designing a stem-cell based clinical approach, there is accumulating evidence from recent (pre-)clinical studies that other issues may also be at stake. For instance, the choice of stem cells to be used and its precise mechanism of action, the need/possibility for concurrent tissue regeneration in case of irreversible tissue loss, the differentiation degree and specific vascular identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
75
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 95 publications
2
75
0
2
Order By: Relevance
“…Unfortunately, clinical trials based on growth factor delivery have not yielded the expected results, thereby exposing the need for alternatives (5,13). Peripheral vascular disease (PVD) caused by inadequate blood supply to the limbs is a severe health Evidence indicating that adult vasculogenesis-vessel formation from endothelial progenitor cells (EPC)-is a problem in the Western world, affecting 3-10% of the population above the age of 60 (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, clinical trials based on growth factor delivery have not yielded the expected results, thereby exposing the need for alternatives (5,13). Peripheral vascular disease (PVD) caused by inadequate blood supply to the limbs is a severe health Evidence indicating that adult vasculogenesis-vessel formation from endothelial progenitor cells (EPC)-is a problem in the Western world, affecting 3-10% of the population above the age of 60 (5).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, clinical trials based on growth factor delivery have not yielded the expected results, thereby exposing the need for alternatives (5,13). Peripheral vascular disease (PVD) caused by inadequate blood supply to the limbs is a severe health Evidence indicating that adult vasculogenesis-vessel formation from endothelial progenitor cells (EPC)-is a problem in the Western world, affecting 3-10% of the population above the age of 60 (5). Therapeutic revascuprocess that contributes to therapeutic neovascularization (6) has fueled the interest in the use of this alternalarization techniques, like laser revascularization, endovascular treatment, or bypass surgery, can in some cases tive paradigm for therapeutic revascularization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have demonstrated the safety, feasibility, and efficacy of intracoronary and intramuscular infusion of adult BMMNCs in patients with peripheral arterial disease, acute myocardial infarction, and ischemic cardiomyopathy. 1,2 However, despite the excitement surrounding the possible clinical use of BMMNCs, in atherosclerosis, diabetes mellitus, and other risk factors for cardiovascular diseases the availability of bone marrow and progenitor cells is reduced and their function impaired to varying degrees. 1,2 Moreover, the safety of BMMNCs treatment has been questioned by studies that found an increase in atherosclerotic plaque size after BMMNCs treatment.…”
mentioning
confidence: 99%
“…1,2 However, despite the excitement surrounding the possible clinical use of BMMNCs, in atherosclerosis, diabetes mellitus, and other risk factors for cardiovascular diseases the availability of bone marrow and progenitor cells is reduced and their function impaired to varying degrees. 1,2 Moreover, the safety of BMMNCs treatment has been questioned by studies that found an increase in atherosclerotic plaque size after BMMNCs treatment. 3 This potentially hazardous dual effect of therapeutic neovascularization on atherogenesis is explained by the many common pathways of both mechanisms and has been named the Janus phenomenon.…”
mentioning
confidence: 99%